Celebrating the 21st anniversary of empowerment evaluation with our critical friends. (August 2017) - Fetterman, David; Wandersman, Abraham
Highlights: Empowerment evaluation celebrates its 21st anniversary. It operates in over 16 countries, from squatter settlements to Google. Donaldson, Scriven, Patton, and Alkin comment on the approach. Contributors and proponents of empowerment evaluation adopt a critical friend's perspective. Abstract: This special topic edition of E&PP presents the insights of luminaries in the field who have helped shape empowerment evaluation with their critiques, concerns, and congratulations. We celebrate their contributions to empowerment evaluation. This special topic edition of E&PP presents their comments about an evaluation approach that, according to president Stewart Donaldson, has "gone viral" across the globe (Donaldson, 2015). To set the stage for these critical friends' comments, additional context for their discussion is provided. In addition, this special topic edition concludes with a brief comment on their thoughts.